Determinants of Brand Equity at FPT Polytechnic College, Ho Chi Minh City - Thi Ha Trang Le; Tran Phuoc Nguyen (Journal of Business and Behavioural Entrepreneurship, 2025)
This research investigates the factors influencing brand equity of FPT Polytechnic College in Ho Chi Minh City, with the objective of enhancing its competitive position and student recruitment. The study aims to elevate the institution's standing among its student body and key stakeholders. The investigation addresses a gap in the current literature by identifying specific factors that influence brand equity in higher education, while proposing strategies to enhance it. It is important to note that the study has limitations, including a constrained survey scope and the absence of comparative analyses with other institutions. The research employed a mixed-methods approach, utilizing both qualitative and quantitative techniques. Data was collected from a sample of 336 valid respondents, comprising current and former students, and subsequently analyzed using various statistical methods. The study identified seven key factors impacting brand equity, with Perceived Quality and Brand Association emerging as the most significant. The research concludes that strong brand equity contributes to institutional credibility, thereby fostering increased trust among parents and prospective students.